Semiotic Analysis of Gender Representation in Film Traveler's Hijab: Love Sparks in Korea - Natasha, Rizkya Adelia; Salsyabila, Sarah; Tawang, Nur Asia (HUMANISMA : Journal of Gender Studies, 2023)
Films as part of mass media have a big impact on human life and tend to depict women as weak, helpless, and targets of crime. In the film "Jilbab Traveler: Love Sparks in Korea," the character of a Muslim female traveler becomes a representation of a woman wearing a hijab in the Islamic religion. This film tells the story of the adventures of a Muslim woman who travels around the world wearing her hijab, creating an image of a successful modern Muslim woman and becoming an inspiration for Muslim women today. The author wants to explore gender representation using a qualitative approach and Roland Barthes' semiotic analysis. The focus is on how the issue of gender equality is depicted in the film and the efforts for gender equality contained in it. The analysis stage was carried out by watching the film in its entirety, capturing the screen on relevant scenes related to the representation of gender equality, and then analyzing it using Roland Barthes' semiotic concept, which considers the denotative, connotative, and mythical meanings contained in the scene. The results show that the main character, Rania, succeeded in achieving her dreams by daring to explore the world without fear, but the semiotic analysis also revealed gender stereotypes attached to several characters. This analysis shows how the film constructs, reproduces, or responds to gender norms in a cultural context and opens up space for understanding gender dynamics and cultural identity in various conditions.Film sebagai bagian dari media massa memiliki dampak besar pada kehidupan manusia dan cenderung menggambarkan perempuan sebagai sosok yang lemah, tidak berdaya, dan menjadi target kejahatan. Dalam film "Jilbab Traveler: Love Sparks In Korea", tokoh penjelajah muslimah menjadi representasi dari wanita berjilbab dalam agama Islam. Film ini mengisahkan petualangan seorang wanita muslim yang mengelilingi dunia dengan jilbabnya, menciptakan gambaran sosok wanita muslimah modern yang sukses dan menjadi inspirasi bagi perempuan Muslim masa kini. Penulis ingin mengeksplorasi representasi gender dengan menggunakan pendekatan kualitatif dan analisis semiotika Roland Barthes. Fokusnya adalah bagaimana isu kesetaraan gender tergambar dalam film tersebut dan usaha-upaya kesetaraan gender yang terdapat di dalamnya. Tahapan analisis dilakukan dengan menonton film secara menyeluruh, menangkap layar pada adegan yang relevan terkait representasi kesetaraan gender, dan kemudian menganalisisnya menggunakan konsep semiotika Roland Barthes, yang mempertimbangkan makna denotatif, konotatif, dan mitos yang terkandung dalam adegan tersebut. Hasilnya menunjukkan bahwa tokoh utama, Rania, berhasil menggapai cita-citanya dengan berani menjelajahi dunia tanpa rasa takut, tetapi analisis semiotik juga mengungkap stereotip gender yang melekat pada beberapa karakter. Analisis ini memperlihatkan bagaimana film tersebut membangun, mereproduksi, atau menanggapi norma-norma gender dalam konteks budaya, serta membuka ruang untuk memahami dinamika gender dan identitas budaya dalam berbagai kondisi.